Using the 21‐gene assay from core needle biopsies to choose neoadjuvant therapy for breast cancer: A multicenter trial - Bear, Harry D.; Wan, Wen; Robidoux, André; Rubin, Peter; Limentani, Steven; White, Richard L.; Granfortuna, James; Hopkins, Judith O.; Oldham, Dwight; Rodriguez, Angel; Sing, Amy P. (Journal of surgical oncology, 2017)
Objective We hypothesized that the Oncotype Dx® 21‐gene Recurrence Score (RS) could guide neoadjuvant systemic therapy (NST) to facilitate breast conserving surgery (BCS) for hormone receptor positive (HR+) breast cancers. Methods This study enrolled patients with HR+, HER2‐negative, invasive breast cancers not suitable for BCS (size ≥ 2 cm). Core needle biopsy blocks were tested. For tumors with RS < 11, patients received hormonal therapy (NHT); patients with RS > 25 tumors received chemotherapy (NCT); patients with RS 11‐25 were randomized to NHT or NCT. Primary endpoint was whether 1/3 or more of randomized patients refused assigned treatment. Results Sixty‐four patients were enrolled. Of 33 patients with RS 11‐25, 5 (15%) refused assignment to NCT. This was significantly lower than the 33% target (binomial test, P = 0.0292). Results for clinical outcomes (according to treatment received for 55 subjects) included successful BCS for 75% of tumors with RS < 11 receiving NHT, 72% for RS 11‐25 receiving NHT, 64% for RS 11‐25 receiving NCT, and 57% for RS > 25 receiving NCT. Conclusions Using the RS to guide NST is feasible. These results suggest that for patients with RS < 25 NHT is a potentially effective strategy.